Influence on Rheology and Microstructure of Nanosilica and Modified Polycarboxylate in Water‐Glass‐Activated Fly Ash/Ground Granulated Blast Furnace Slag Geopolymers . Issue 1 (2nd January 2023) - Vanitha, N.; Revathi, T.; Jeyalakshmi, R.
Abstract: This study establishes the effect of nano silica (NS) in the alkali activator on the behaviour of rheology and microstructure of Alkali activated material. The rheological behaviour of the Fly ash (FA)‐Ground granulated blast furnace slag (GGBS) (4 : 1) activated using water glass of Ms 1.1 (SiO2 /Na2 O), with nano silica (NS), Modified Poly carboxylate (MPC) was studied and the link between the composition and fundamental behaviour are reported. A total of 12 mortar mixtures were cast by varying the dose of NS from 0–3 %, and MPC 0–2.5 % and their fresh properties were obtained from the slump, setting time and flow value. The compressive strengths of mortars showed an increasing trend from 40 to 55 MPa with NS addition from 0–2.5 wt% at an optimal dose of 1 % MPC. The suspensions with and without NS fit well with Herschel‐Bulkley model, in the hysteresis cycle. The incorporation of NS at a threshold value below 2 % leads to a drastic change in viscosity with increasing time at a constant shear rate, implying. a thixotropy with yield‐type behaviour that are associated with the rebuilding of the flocculated structure with time. The nucleating effect of NS progressively improved the strength of the mix, due to the formation of compact gel microstructure which was confirmed by SEM micrograph with fewer pores. NS improves CSH gel and gelatinous silica phase in the matrix as is evident from the formation of the SiQ 4 structural unit as it is absent in control. The poly (Sialate) structural unit in geopolymer ascertained from 29 Si, 27 Al MAS NMR chemical shift corresponds to Alq 3 (3Si) with the absence of remnant Al(IV) peak of Fly ash in NS (2.%) activated samples. Abstract : This study describes the effect of nano silica (NS) in the alkali activator on therheology and micro structure of Fly ash (FA)‐Ground granulated blast furnace slag (GGBS) (4 : 1) geopolymer. The relation between compositional changes during the geopolymerisation under water glass of Ms 1.1 (SiO2/Na2O), with nano silica (NS), Modified Poly carboxylate (MPC) superplasticizer investigated from multiple characterisation techniques to the observed mechanical strength was established.